The Effect of Sharia Financial Inclusion on Gross Regional Domestic Product in Indonesia for the 2019-2023 Period - Rizkia, Tita; Nurdin, Ade Ali (Journal of Applied Islamic Economics and Finance, 2025)
This study aims to analyze the influence of Sharia financial inclusion on the Gross Regional Domestic Product (GRDP) in Indonesia from 2019 to 2023. Sharia financial inclusion is measured using three main dimensions: accessibility, availability, and usage, proxied by indicators from Sharia Commercial Banks (BUS), Sharia Business Units (UUS), and Sharia People's Financing Banks (BPRS) across 33 provinces. This quantitative study uses secondary data from OJK, Bank Indonesia, and BPS, and applies panel data regression via STATA 17. The findings show that both partial and simultaneous influences of the inclusion dimensions significantly affect GRDP growth. These results imply that improving access, availability, and usage of Sharia financial services is crucial for boosting regional economic development and achieving Indonesia's vision as a global Islamic economic hub.